Role of cathepsin D activation in major adverse cardiovascular events and new-onset heart failure after STEMI - ERCAN, ÇİLEM; YAMAÇ, AYLİN HATİCE; YAMAÇ, AYLİN HATİCE; ERCAN, ÇİLEM; BACAKSIZ, AHMET (My University, 2015)
Increased serum levels of the activated aspartic lysosomal endopeptidase cathepsin D (CatD) have been found in patients with acute myocardial infarction (AMI). However, to date there have been no analyses of clinical follow-up data measuring the enzyme course and its role in the development of post-MI heart failure. This study aimed to evaluate the role of serum CatD activity in the development of heart failure in patients with ST-segment elevation acute myocardial infarction (STEMI).